Combining ability analysis in anthracnose-resistant introgression inbreds and developing improved resistant lines of pepper (Capsicum annuum L.) - Patcharapan Saengarun; Patcharaporn Suwor; Hathaipat Inprasert; Nattika Kumsee; Wen Shi Tsai; Suchila Techawongstien; Tanyarat Tainta; Sanjeet Kumar; Nakarin Jeeatid; Orawan Chatchawankanphanich; Somsak Kramchote (Scientia Horticulturae, 2024)
• ANT4 ( C. annuum L.) introgression line derived from C. baccatum PBC80 was resistant to the aggressive strain of Colletotrichum acutatum causing chili anthracnose. • Additive gene effect on anthracnose disease triat was inherited. • SSR-HpmsE032 marker associated with resistance was more effective in the early generation selection than selection in late generation. • New resistant F 5 lines with improved fruit type could be directly released as varieties after field evaluation or it could be used to develop male sterility system for breeding of hybrid varieties. Chili peppers ( C. annuum L.) are a commercial spice crop in the tropics. In Thailand, chili pepper is a cash crop for farmers and has cultural significance in Thai cuisine. Anthracnose disease caused by Colletotrichum spp. is responsible for a significant reduction in the marketable fruit yield of chili peppers. In this study, we tested the combining abilities of anthracnose-resistant chili pepper lines possessing resistance introgression genome segments from C. chinense (PBC932) and C. baccatum (PBC80). Six parental inbreds developed from two resistant donors PBC80 and PBC932 were crossed in a haft-diallel fashion to develop 15 cross combinations during 2018. In 2019, seeds of 21 genotypes comprising six parents and 15 F 1 s were planted in Randomized Complete Block Design (RCBD) and data on plant characteristics, fruit yield and yield components were recorded. Detached fruits were screened against anthracnose causing aggressive species ( C. acutatum ). ANT4 showed the lowest disease lesion size and lowest GCA value at green and red fruit stages, containing resistance from PBC80. Additionally, the general combining ability (GCA) and specific combining ability (SCA) were significantly different at the green fruit stage, with the SCA component greater than GCA. Based on GCA and SCA estimates, ANT4 was selected and crossed to three highly susceptible cultivars (Yodsonkeam 80, Num, and Jindanil 80). The crosses were advanced and 10 F 5 lines were developed through marker-assisted selection (MAS) for resistance genes. The MAS was more useful for selecting resistance at the green fruit stage. We also found that MAS was more effective in F 2 progenies compared to F 5 progenies. Finally, we selected 10 new pure lines and evaluated them at the farmer's field. AF1, AF6, and AF7 were highly resistant to anthracnose, a more desirable good fruit type and high yield.
Keywords: Plant Virus Research Studies; Plant Pathogens and Resistance; Plant Genetic and Mutation Studies